Prediction of sound absorption of waste tyre textile fibre composite material - Ružickij, Robert; Grubliauskas, Raimondas (International Conference “Environmental Engineering”, 2023)
Waste Tyre Textile Fibres (WTTF) are one of the main components of end-of-life tyres. During the recycling process, it is been separated from the rubber and the metal parts. According to the EU Directive on Landfills 1999/31/EC end-of-life tyres may not be accepted by the facility, and it is encouraged to recycle them. Rubber has been successfully recycled and reused for asphalt and playground surfaces production, while metals could be remelted and used again. However, there is a lack of knowledge how to use WTTF. In this research we are proposing WTTF composite material for sound absorption applications. To bind the fibres, polyurethane resin was used. Different percentage by weight of binder was used to determine its’ effect on sound absorption coefficient. The sound absorption coefficient determination method is based on the experimental data based on the ISO 10534-2 standard, and Delany-Bazley-Miki (DBM) acoustic prediction model of fibrous materials, using non-acoustic parameters of the material. The results showed that DBM model accuracy rate varied from 4.9 to 12.7%. Such result indicated that DBM acoustic model has errors in prediction. The aim of this study is to predict the sound absorption coefficient using Delany-Bazley-Miki acoustic model and compare to the experimental study using impedance tube.
Keywords: composite material; Delany-Bazley-Miki acoustic model; reuse; sound absorption coefficient; Waste Tyre Textile Fibres